Optimal Design and Operation of Fast Charging Station for Electric Vehicle Via Renewable Energy in Wadi El-Natrun-El Alamein Road, Egypt - Enany, Mohamed A; Farahat, Mohamed A; Otay, Mohamed Ibrahim (International Journal of Sustainable Energy and Environmental Research, 2021)
The cost of Electric Vehicle Charging Station (EVCS) infrastructure is one of the problems which stand as a barrier in the way of widespread Electric Vehicles (EV). In this paper, the optimal design and operation of a renewable-powered EVCS will be introduced with minimizing cost and air pollution. By considering the station located in isolated area and will be supplied by hybrid Energy Sources. Configuration, sizing, economic optimization, operation and its effect on the environment are discussed. The proposed hybrid micro-grid consists of, photovoltaic panels, storage batteries, wind turbines, biogas generator and also a diesel generator. The case study of this work is to satisfy the 1056 KWh/day demand of EVCS for using at the selected site. Five different configurations of energy sources are studied to get the optimum case. HOMER software is used to implement the simulation model; the model is based on economic and environmental factors. Finally, the study introduces a cost-effective, socially and sustainable accepted design that can be useful in specifying the appropriateness of optimal design for other EVCSs.